cho a-b=1
cm a^3 - b^3 = 1+3ab
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:a+b=1
<=>(a+b)^3=1^3
<=>a^3+3a^2.b+3a.b^2+b^3=1
<=>a^3+b^3+3ab(a+b)=1
mà a+b=1=>a^3+b^3+3ab=1=>a^3+b^3=1-3ab(dpcm)
Ta có:a+b=1
<=>(a+b)^3=1^3
<=>a^3+3a^2.b+3a.b^2+b^3=1
<=>a^3+b^3+3ab(a+b)=1
mà a+b=1=>a^3+b^3+3ab=1=>a^3+b^3=1-3ab(dpcm)
1) \(2\left(3x-1\right)< 2x+4\)
\(\Leftrightarrow6x-2< 2x+4\)
\(\Leftrightarrow4x< 6\)
\(\Leftrightarrow x< \frac{3}{2}\).
2) \(4x-8\le3\left(2x-1\right)-2x+1\)
\(\Leftrightarrow4x-8\le6x-3-2x+1\)
\(\Leftrightarrow0x\ge-6\)(đúng với mọi \(x\))
4) \(\left(x-3\right)\left(x+3\right)< \left(x+2\right)^2+3\)
\(\Leftrightarrow x^2-9< x^2+4x+4+3\)
\(\Leftrightarrow4x>-16\)
\(\Leftrightarrow x>-4\)
5) \(\left(x-3\right)^2< x^2-5x+4\)
\(\Leftrightarrow x^2-6x+9< x^2-5x+4\)
\(\Leftrightarrow x>5\).
6) \(\left(x-3\right)\left(x+3\right)\le\left(x+2\right)^2+3\)
\(\Leftrightarrow x^2-9\le x^2+4x+4+3\)
\(\Leftrightarrow4x\ge-16\)
\(\Leftrightarrow x\ge-4\)
Ta có 1 + 2 + 3 + ... + 100 = 5050
Ta có 15 + 25 + ... + 1005
= (15 + 1005) + (25 + 995) + ... + (505 + 515)
= 101.A + 101.B + ... + 101.C
= 101(A + B + ... + C) \(⋮\)101 (1)
Lại có 15 + 25 + .. + 1005
= (15 + 995) + (25 + 985) + .... + (495 + 515) + 505 +1005
= 100.A + 100.B + .... + 100.C + 505 + 1005
= 50.(2A + 2B + ... + 2C + 504 + 504.25) \(⋮\)50 (2)
Từ (1) và (2) => 15 + 25 + .. + 1005 \(⋮\)50.101 = 5050
<=> 15 + 25 + .. + 1005 \(⋮\)1 + 2 + 3 + ... + 100
\(\left(a-b\right)\left(a^2+ab+b^2\right)\)
\(=a^3+a^2b+ab^2-a^2b-ab^2-b^3\)
\(=a^3-b^3\)
(a-b).(a2+ab+b2)
= (a3+a2b+ab2) - (a2b+ab2+b3)
= a3+a2b+ab2-a2b-ab2-b3
= (a3-b3) + (a2b-a2b) + (ab2-ab2)
= a3-b3
a) \(\sqrt{\frac{1}{3-2x}}\)có nghĩa <=> \(\frac{1}{3-2x}>0\Leftrightarrow3-2x>0\Leftrightarrow x>\frac{3}{2}\)
b) \(\sqrt{\frac{x+2}{x^2+1}}\)có nghĩa <=> \(\frac{x+2}{x^2+1}\ge0\Leftrightarrow x+2\ge0\Leftrightarrow x\ge-2\)
c) \(\sqrt{\frac{x+5}{x-7}}\)có nghĩa <=> \(\frac{x+5}{x-7}\ge0\Leftrightarrow\orbr{\begin{cases}x>7\\x\le-5\end{cases}}\)
Tôi chết chx ???
\(a^3-b^3\)
\(\left(a-b\right)\left(a^2+ab+b^2\right)\)
\(a^2+ab+b^2\)
\(a^2-2ab+b^2+3ab\)
\(\left(a-b\right)^2+3ab\)
\(1^2+3ab=1+3ab=VP\)
\(< =>ĐPCM\)